Preparation and characterization of linear low denstity polyethylene LLDPE/thermoplastic starch (TPS)/banana fiber composites - Abduati Salem Abrahim Elnaid (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
The blending of linear low density polyethylene (LLDPE) with thermoplastic strach (TPS) and filled with banana fiber (BF) were investigated. Two types of systems were prepared; the LLDPE/TPS matrix with different blend ratio and (LLDPE/TP) (80/20) composites filled with 5 - 30 wt% of BF. Morphological changes using scanning electron microscope (SEM) were observed and its showed that TPS particles are homogenously dispersed in LLDPE matrix.